STUDIPERBANDINGAN OKSIGEN DAN UAP AIR UNTUK MENG-EKSPANSI MAKANAN RINGAN DALAM KONDISI VAKUM - ISMAIL SULAIMAN ' (Jurnal Sagu, 2015)
ABSTRACTThe utilization of oxygen and steam as a snack expansion is one of the new method that have been tested toproduce a quality product. Modification of the structure and materials through the DIC (détente instantanecontrole) as of the fast autovaporasion through the extreme thermodynamic conditions by heating and rapidcooling. Comparison of steam and oxygen is entired particles to be into the material particles influence thecharacteristics and the composition of volumes largely expanded. Capacity expansion through volumes ofmaterial properly occurs properly if steam is used. Using oxygen of expansion with several experimentscannot affect a significant change in the characteristics of the material. Changes in temperature and pressureaffect the rate of expansion of the product, but the moisture content accelerate the expansion process in afood product. These modifications are generally derived from the structural characteristics of the productthat is translated through the expansion of the material conditions and also the value of the rheology ofmaterials. The composition of the structure of a product can be changed by temperature, pressure andvacuum.Key words: hydrogen, steam, DIC, snack, expansion